Efeitos do exercício físico resistido sobre os sistemas purinérgico, colinérgico e oxidativo em modelo experimental de exposição ao lipopolissacarídeo - Miron, Vanessa Valéria (2023)
Lipopolysaccharide (LPS) is a toxin originating from gram-negative bacteria and is widely used in research to induce a range of manifestations ranging from systemic inflammation to generalized infection and memory loss. The purinergic system is related to the immune system, since its enzymes can control the concentration of nucleotides and nucleosides that will bind to receptors and trigger pro- and anti-inflammatory functions. The memory loss caused by LPS may be related to acetylcholine, the main neurotransmitter, and the system that surrounds it, the cholinergic system. In addition to these systems, oxidative stress is also related to the inflammatory and neurotransmitter pathway, which can affect memory and learning. To prevent changes resulting from exposure to LPS, since reversing the inflammatory condition is difficult and generates enormous costs for public health, we use resistance physical exercise in a model of exposure to LPS and focus on the central nervous system. The exercise protocol lasted 12 weeks on a ladder with a frequency of 3 times a week, where there was a progression of load and volume every 3 weeks. After the 72-hour period of the last training session, 2.5 mg/kg of LPS was applied i.p. and the cortex and hippocampus were collected 24 hours after toxin exposure. The analyzes revealed that LPS was able to: 1) increase the activity of purinergic (NTPDase and 5'-nucleotidase) and cholinergic (acetylcholinesterase) enzymes; 2) increase the density of P2X7R, NLRP3, Caspase1, IL-1β, IL-6, TNF-α, Iba, H&E; 3) increase levels of TBARS and reactive species; 4) reduce exploration time for the new object in the memory test; 5) decrease the density of BDNF. Resistance physical exercise was able to prevent all these changes in addition to: 1) increasing the density of α-7R, M1R, BDNF and Nestin; 2) increase levels of protein thiols and; 3) decrease the density of A2AR. These results confirm that exercise has anti-inflammatory, antioxidant and neuroprotective properties and demonstrate the involvement of the purinergic, cholinergic and oxidative pathways in this protective mechanism. With these good results, the aim is to encourage research related to the topic, as well as the regular practice of physical exercise by the population.